2016
DOI: 10.1002/adma.201604018
|View full text |Cite|
|
Sign up to set email alerts
|

Direct Fabrication of 3D Metallic Networks and Their Performance

Abstract: In the RhB Degradation part of the Experimental Section, the concentration of RhB used in the experiments was incorrectly reported. The concentration is hereby corrected to read 10 −5 M. The text should thus read: "The experiments were performed at ambient temperature and pressure using Xe lamp, 175 W (Lambda). The concentration of RhB in all solutions was C 0 = 10 −5 M." The main conclusions are unaffected and the experiments will still work at the lower concentration. The authors apologize for any inconvenie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(75 citation statements)
references
References 30 publications
1
74
0
Order By: Relevance
“…The dissolution of the less noble component is coupled with diffusion and aggregation of the more noble metal element at the solid/liquid interface: the overall process leaves behind a porous metal structure (a metal “sponge”) that can be enriched or mainly composed of the nobler element . Nanoporous metals prepared via selective dealloying of solid solutions possess a three‐dimensional (3D) structure of randomly interpenetrating ligaments/pores with sizes between a few nm to several tens of μm; these structural features can be precisely tuned by varying the preparation conditions (such as alloy composition, dealloying time, temperature, and electrochemical parameters) or by subsequent a thermal coarsening step …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dissolution of the less noble component is coupled with diffusion and aggregation of the more noble metal element at the solid/liquid interface: the overall process leaves behind a porous metal structure (a metal “sponge”) that can be enriched or mainly composed of the nobler element . Nanoporous metals prepared via selective dealloying of solid solutions possess a three‐dimensional (3D) structure of randomly interpenetrating ligaments/pores with sizes between a few nm to several tens of μm; these structural features can be precisely tuned by varying the preparation conditions (such as alloy composition, dealloying time, temperature, and electrochemical parameters) or by subsequent a thermal coarsening step …”
Section: Introductionmentioning
confidence: 99%
“…[24] Nanoporous metals prepared via selective dealloying of solid solutions possess a three-dimensional (3D) structure of randomly interpenetrating ligaments/pores with sizes between a few nm to several tens of mm; these structural features can be precisely tuned by varying the preparation conditions (such as alloy composition, dealloying time, temperature, and electrochemical parameters) or by subsequent a thermal coarsening step. [18,[25][26][27][28][29] In spite of the large application in heterogeneous catalysis, there is however still a comparably low number of studies on nanoporous metal co-catalysts for photocatalytic applications. Nguyen et al have reported on porous Au, [30] AuPt, [31] or PtPd [32] nanoparticles produced on TiO 2 nanotubes (NTs) by chemical dealloying of dewetted-alloyed nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Adapted with permission. [56] Copyright 2016, Wiley-VCH. SEM images and digital photos (inset) of d) the gold nanoparticle amyloid aerogel and e) the gold crystal amyloid aerogel.…”
Section: Sacrificial Templatingmentioning
confidence: 99%
“…In sharp contrast with regular templating methods where materials conformally grow on the as-used templates, Salomon's group found a distinguishing phenomenon when a silica aerogel was applied as substrate. [56] As illustrated in Figure 4c, after physical vapor deposition (PVD), a wide range of metals, including Au, Ag, Pt, and nonnoble metals (e.g., Fe, Al, Cu, Ti), formed macroscopic 3D networks on the surface of porous silica aerogels. These foams were usually micrometer-thick (up to 4 µm for gold) and showed an average ligament size of several tens of nanometers.…”
Section: Silica Aerogel Templatingmentioning
confidence: 99%
“…[15,16] Since then, great efforts had been made to simplify the preparation procedures, especially drying process, for the facile and cost-effective preparation of aerogels. [17][18][19] Meanwhile, the types of aerogels were greatly enriched, including nonsilica oxide-based aerogels, [20][21][22][23][24][25][26][27][28] chalcogenide aerogels, [29][30][31][32][33][34] organic aerogels, [35,36] carbon aerogels, [37][38][39][40][41][42] metallic aerogels, [43][44][45][46][47][48][49][50][51][52][53][54] hybrid aerogels, [55,56] etc. In the past few years, intensive studies on application and industrialization of the aerogels sprang up, demonstrating great application potential of aerogels.…”
Section: Doi: 101002/smll201902826mentioning
confidence: 99%